A process for producing composite special-shaped yarn with high bonding strength
Through various technical means such as preoxidation, thermal composite, rolling welding, polishing and grinding, nitrogen purge and spray lubricant, high binding fastness AgCdO/AgNi10 composite special-shaped wire was prepared, which solved the problem of unstable material bonding fastness in traditional methods, met the performance requirements of high-end applications, and was environmentally friendly.
Patent Information
- Application Number
- CN202510174519.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The bonding fastness of AgCdO/AgNi10 special-shaped wire produced by traditional composite methods is unstable, and it is prone to interlayer peeling or performance degradation, which cannot meet the high requirements for material performance in high-end applications.
AgCdO was prepared by pre-oxidation process, and a uniform AgCdO/Ag composite layer was heat-combined with Ag, and then rolling welding was performed in air to form an AgCdO/Ag-AgNi10 composite alloy. The alloy surface is then polished and polished, nitrogen purged and sprayed with lubricant, and finally, composite special-shaped wires with high bond fastness are obtained by filament separation, drawing and forming rolling.
Through the combined application of multiple steps and multiple technical means, the bonding fastness and performance of composite special-shaped wires are significantly improved, meet the needs of high-end application fields, and the use of environmentally friendly materials is used to reduce environmental pollution.
Smart Images

Figure CN119634483B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material processing and welding, and relates to a process method for high-bonding-strength composite special-shaped wire. Background Art
[0002] AgCdO and AgNi10 are two important silver-based alloy materials with good electrical and thermal conductivity and anti-oxidation ability. When the traditional composite method is used to produce special-shaped wires of these two materials, there is often a problem of unstable bonding strength, which affects the performance and life of the materials.
[0003] At present, the commonly used method is to use cold pressing or simple heat treatment technology to produce AgCdO / AgNi10 composite shaped wire. However, these methods are difficult to ensure the bonding strength and uniformity between the two materials during the production process.
[0004] The AgCdO / AgNi10 shaped wire produced by traditional composite method has unstable bonding strength and is prone to problems such as interlayer delamination or performance degradation, which cannot meet the high requirements of material performance in high-end application fields. Summary of the invention
[0005] The purpose of the present invention is to provide a process method for producing composite special-shaped yarns with high bonding strength, which has the characteristic of high bonding strength.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A process for producing composite shaped yarn with high bonding strength, the specific process of the process is as follows:
[0008] S1: First, the AgCd composite strip is prepared into AgCdO through a pre-oxidation process, and then AgCdO and Ag are thermally compounded to form a uniform AgCdO / Ag composite layer;
[0009] S2: placing the prepared AgCdO / Ag composite layer and AgNi10 in air, and rolling-welding the two to obtain an AgCdO / Ag-AgNi10 composite alloy;
[0010] S3: polishing and grinding the surface of the AgCdO / Ag-AgNi10 composite alloy, purging with nitrogen after the polishing and grinding, spraying lubricant on the surface of the alloy, dividing and drawing the alloy, and then forming and rolling the alloy to obtain composite shaped wire.
[0011] Furthermore, the pre-oxidation process parameters in S1 are oxygenation in an oxygen atmosphere at a temperature of 700-800° C. for 35-45 hours.
[0012] Furthermore, the thermal composite process parameters in S1 are 630-680° C. and a tape speed of 1.2-1.8 m / min.
[0013] Furthermore, the rolling welding parameters in S2 are: rotation speed 300~400r / min, welding speed 80~120mm / min, rolling head inclination angle 0.5°, downward pressure 0.3~0.5mm, welding current 5.5~9.5KA, and welding pressure 35~45Kgf.
[0014] Furthermore, the polishing parameters in S3 are: first use a grinding head composed of 500-mesh elastic modules to polish at 1-2 MPa for 1 hour, and then use a grinding head composed of 2000-mesh elastic modules to polish at 0.3-0.5 MPa for 0.5 hour.
[0015] Furthermore, the flow rate of nitrogen purge in S3 is 20 m / s, and the purge time is 0.5 h.
[0016] Furthermore, the lubricant preparation method in S3 is as follows:
[0017] Graphite and molybdenum disulfide are mixed in a mass ratio of 1:1, ground in a ball mill at a speed of 400 r / min for 1 hour to obtain a mixture with a particle size of 800 mesh, dispersed in glycerol with a solid-liquid mass ratio of 2:1, and then 2wt% of silane coupling agent KH550 is added to the solid-liquid mixture, and stirred at a speed of 200 r / min for 1 hour to obtain the lubricant.
[0018] Furthermore, the spraying parameters of the lubricant are a spraying distance of 100 mm and a spraying rate of 60 mm / s.
[0019] Furthermore, the diameter of the wire obtained by the wire splitting process in S3 is 0.4-0.6 mm.
[0020] Furthermore, the diameter of the wire obtained by the drawing process in S3 is 0.2-0.3 mm.
[0021] The process of the present invention combines multiple technical means such as hot pressing, rolling welding, polishing, nitrogen purging, spraying lubricant, wire separation, drawing and forming rolling to form a complete set of composite shaped wire preparation process. This multi-step and multi-technical combination application makes the composite shaped wire prepared by the present invention have higher performance and bonding strength.
[0022] First, the AgCd composite strip is prepared into AgCdO through a pre-oxidation process, and then AgCdO and Ag are thermally composited to form a uniform AgCdO / Ag composite layer. A uniform AgCdO / Ag composite layer is formed, and the composite type is comprehensive composite, that is, AgCdO completely covers the Ag surface. The composite layer prepared by this method not only improves the overall performance of the material, but also maintains the respective characteristics of AgCdO and Ag, providing a high-quality foundation for subsequent rolling welding.
[0023] The present invention further uses a roll welding process, which is carried out in air to avoid oxidation and pollution, and improve the welding quality. Roll welding is an efficient and energy-saving welding method that can form high-quality welds. By accurately controlling the parameters of roll welding, the stability and controllability of the welding process can be ensured, such as Figure 1 As shown, a high-quality AgCdO / Ag-AgNi10 composite alloy is obtained, with the Ag layer located in the middle. The AgCdO / Ag composite layer is combined with the AgNi10 alloy to form a composite alloy with higher strength and bonding. The rolling welding process is referenced Figure 3 .
[0024] Polishing and grinding the composite alloy surface can remove surface defects and impurities and improve surface smoothness and flatness. This treatment not only helps to improve the appearance quality of the composite profiled wire, but also improves its compatibility with subsequent processing steps. Using nitrogen purge can further remove surface residues and provide a clean surface for subsequent drawing and rolling processes. At the same time, spraying lubricants on the alloy surface can reduce friction resistance during drawing and rolling, improving processing efficiency and product quality.
[0025] Finally, through wire separation, drawing and forming rolling, such as Figure 2 As shown, composite shaped yarn with high bonding strength can be obtained. Figure 2 The middle coordinate scale is 200 μm. The composite shaped wire of the present invention can be customized according to needs to meet the needs of different application scenarios.
[0026] Graphite and molybdenum disulfide are both outstanding solid lubricants. They have excellent lubricating properties and can form a highly adhesive lubricating film on the metal surface, significantly reducing the friction coefficient and wear degree. By mixing graphite and molybdenum disulfide in a mass ratio of 1:1 and grinding to 800 mesh, their dispersion and uniformity are further improved, thereby enhancing the lubrication effect; both graphite and molybdenum disulfide have high stability, are not easy to react chemically with metals, and can maintain good lubrication properties at high temperatures.
[0027] In the present invention, the mixture is dispersed in glycerol, and silane coupling agent KH550 is added for stirring, which further improves the stability and heat resistance of the lubricant, so that it can play a better role in the preparation process of the composite special-shaped wire, and graphite and molybdenum disulfide are both environmentally friendly materials and have no pollution to the environment.
[0028] In the preparation process of composite shaped wire, the use of the lubricant provided by the present invention can significantly reduce the friction resistance in the steps of wire separation, drawing and forming rolling, thereby improving production efficiency. The graphite and molybdenum disulfide in the lubricant can form a lubricating film on the metal surface to protect the metal from wear and scratches, thereby improving the surface quality and appearance of the composite shaped wire. At the same time, since the lubricant has good stability and heat resistance, it can maintain good lubrication performance at high temperatures, thereby ensuring that the composite shaped wire will not be damaged due to frictional heat during the preparation process.
[0029] Beneficial effects of the present invention:
[0030] (1) The present invention forms a complete set of composite shaped wire preparation process through pre-oxidation, thermal composite, rolling welding, polishing, nitrogen purging, spraying lubricant, wire separation, drawing and forming rolling. The AgCdO / Ag composite layer is firstly prepared by pre-oxidation and thermal composite process, and then the AgCdO / Ag-AgNi10 composite alloy is prepared by rolling welding, so that the composite shaped wire prepared by the present invention has higher performance and bonding strength;
[0031] (2) In the present invention, graphite and molybdenum disulfide are dispersed in glycerol in a mixture in a mass ratio of 1:1, and a silane coupling agent KH550 is added and stirred to obtain a lubricant. The lubricant has better stability and heat resistance, so that it can play a better role in the preparation process of composite shaped wires. In addition, graphite and molybdenum disulfide are both environmentally friendly materials and do not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0033] Figure 1 Cross-section of AgCdO / Ag-AgNi10 composite alloy;
[0034] Figure 2 The cross-section of the obtained composite shaped wire;
[0035] Figure 3 Schematic diagram of the roll welding process. DETAILED DESCRIPTION
[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0037] Example 1
[0038] A process for producing composite shaped yarn with high bonding strength, the specific process of the process is as follows:
[0039] S1: First, the AgCd composite strip is prepared into AgCdO by a pre-oxidation process, the pre-oxidation process parameters are oxygenation in an oxygen atmosphere at a temperature of 750°C for 40 hours, and then AgCdO and Ag are thermally composited to form a uniform AgCdO / Ag composite layer, the thermal composite process parameters are at 650°C and a tape speed of 1.5m / min;
[0040] S2: The prepared AgCdO / Ag composite layer and AgNi10 were placed in air and roll-welded. The roll-welding parameters were as follows: rotation speed 350r / min, welding speed 100mm / min, rolling head inclination angle 0.5°, downward pressure 0.4mm, welding current 8KA, welding pressure 40Kgf, to obtain AgCdO / Ag-AgNi10 composite alloy;
[0041] S3: The surface of the AgCdO / Ag-AgNi10 composite alloy was polished and ground. The polishing and grinding parameters were as follows: first, a grinding head composed of 500 mesh elastic modules was used for grinding at 1.5 MPa for 1 h, and then a grinding head composed of 2000 mesh elastic modules was used for grinding at 0.4 MPa for 0.5 h. After the polishing and grinding treatment, nitrogen was purged. The flow rate of nitrogen purge was 20 m / s, and the purge time was 0.5 h. Lubricant was sprayed on the surface of the alloy. The spraying parameters were spraying distance of 100 mm and spraying rate of 60 mm / s. The wire diameter was 0.5 mm after the wire splitting treatment. The wire diameter was 0.3 mm after the wire drawing treatment. Then, the wire was formed and rolled to obtain composite special-shaped wire.
[0042] Wherein, the lubricant preparation method in S3 is as follows:
[0043] Graphite and molybdenum disulfide are mixed in a mass ratio of 1:1, ground in a ball mill at a speed of 400 r / min for 1 hour to obtain a mixture with a particle size of 800 mesh, dispersed in glycerol with a solid-liquid mass ratio of 2:1, and then 2wt% of silane coupling agent KH550 is added to the solid-liquid mixture, and stirred at a speed of 200 r / min for 1 hour to obtain the lubricant.
[0044] Example 2
[0045] A process for producing composite shaped yarn with high bonding strength, the specific process of the process is as follows:
[0046] S1: First, the AgCd composite strip is prepared into AgCdO by a pre-oxidation process, the pre-oxidation process parameters are oxygenation in an oxygen atmosphere at a temperature of 700°C for 45 hours, and then AgCdO and Ag are thermally composited to form a uniform AgCdO / Ag composite layer, the thermal composite process parameters are at 630°C and a tape speed of 1.2m / min;
[0047] S2: placing the prepared AgCdO / Ag composite layer and AgNi10 in air, and rolling welding the two, the rolling welding parameters are: rotation speed 300r / min, welding speed 80mm / min, rolling head inclination angle 0.5°, downward pressure 0.5mm, welding current 5.5KA, welding pressure 35Kgf, to obtain AgCdO / Ag-AgNi10 composite alloy;
[0048] S3: The surface of the AgCdO / Ag-AgNi10 composite alloy was polished and ground. The polishing and grinding parameters were as follows: first, a grinding head composed of 500 mesh elastic modules was used for grinding at 1 MPa for 1 h, and then a grinding head composed of 2000 mesh elastic modules was used for grinding at 0.3 MPa for 0.5 h. After the polishing and grinding treatment, nitrogen was purged. The flow rate of nitrogen purge was 20 m / s, and the purge time was 0.5 h. Lubricant was sprayed on the alloy surface. The spraying parameters were spraying distance of 100 mm and spraying rate of 60 mm / s. The wire diameter was 0.4 mm after the wire splitting treatment, and the wire diameter was 0.2 mm after the wire drawing treatment. Then, the composite special-shaped wire was formed and rolled.
[0049] Wherein, the lubricant preparation method in S3 is as follows:
[0050] Graphite and molybdenum disulfide are mixed in a mass ratio of 1:1, ground in a ball mill at a speed of 400 r / min for 1 hour to obtain a mixture with a particle size of 800 mesh, dispersed in glycerol with a solid-liquid mass ratio of 2:1, and then 2wt% of silane coupling agent KH550 is added to the solid-liquid mixture, and stirred at a speed of 200 r / min for 1 hour to obtain the lubricant.
[0051] Example 3
[0052] A process for producing composite shaped yarn with high bonding strength, the specific process of the process is as follows:
[0053] S1: First, the AgCd composite strip is prepared into AgCdO by a pre-oxidation process, the pre-oxidation process parameters are oxygenation in an oxygen atmosphere at a temperature of 800°C for 45 hours, and then AgCdO and Ag are thermally composited to form a uniform AgCdO / Ag composite layer, the thermal composite process parameters are at 680°C and a tape speed of 1.8m / min;
[0054] S2: The prepared AgCdO / Ag composite layer and AgNi10 were placed in air and roll-welded. The roll-welding parameters were: rotation speed 400r / min, welding speed 120mm / min, rolling head inclination angle 0.5°, downward pressure 0.3mm, welding current 9.5KA, welding pressure 45Kgf, to obtain AgCdO / Ag-AgNi10 composite alloy;
[0055] S3: The surface of the AgCdO / Ag-AgNi10 composite alloy was polished and ground. The polishing and grinding parameters were as follows: first, a grinding head composed of 500 mesh elastic modules was used for grinding at 2 MPa for 1 h, and then a grinding head composed of 2000 mesh elastic modules was used for grinding at 0.5 MPa for 0.5 h. After the polishing and grinding treatment, nitrogen was purged. The flow rate of nitrogen purge was 20 m / s, and the purge time was 0.5 h. Lubricant was sprayed on the alloy surface. The spraying parameters were spraying distance of 100 mm and spraying rate of 60 mm / s. The wire diameter was 0.6 mm after the wire splitting treatment, and the wire diameter was 0.3 mm after the wire drawing treatment. Then, the wire was formed and rolled to obtain composite special-shaped wire.
[0056] Wherein, the lubricant preparation method in S3 is as follows:
[0057] Graphite and molybdenum disulfide are mixed in a mass ratio of 1:1, ground in a ball mill at a speed of 400 r / min for 1 hour to obtain a mixture with a particle size of 800 mesh, dispersed in glycerol with a solid-liquid mass ratio of 2:1, and then 2wt% of silane coupling agent KH550 is added to the solid-liquid mixture, and stirred at a speed of 200 r / min for 1 hour to obtain the lubricant.
[0058] Comparative Example 1
[0059] This comparative example does not use rolling welding, but only uses conventional cold pressing and bonding, and the remaining steps are consistent with Example 1.
[0060] Comparative Example 2
[0061] In this comparative example, no lubricant is sprayed on the alloy surface, and the remaining steps are consistent with those of Example 1.
[0062] The performance of the embodiments and comparative examples was tested, and a tensile test was performed according to the standard GB / T 228.1-2021, and the bonding conditions at the fracture were observed. The experimental data are summarized in the following table:
[0063]
[0064] Through experimental data and Figure 1 , 2 It can be seen that the composite shaped yarn prepared by the present invention has higher bonding strength, and the addition of lubricant also improves the performance of the composite shaped yarn.
[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for producing composite shaped yarn with high bonding strength, characterized in that: The specific process of the process is as follows: S1: First, the AgCd composite strip is prepared into AgCdO through a pre-oxidation process, and then AgCdO and Ag are thermally compounded to form a uniform AgCdO / Ag composite layer; S2: placing the prepared AgCdO / Ag composite layer and AgNi10 in air, and rolling welding the two to obtain AgCdO / Ag-AgNi10 composite alloy, wherein the rolling welding parameters are: rotation speed 300-400 r / min, welding speed 80-120 mm / min, rolling head inclination angle 0.5°, downward pressure 0.3-0.5 mm, and welding current 5.5-9.5 KA; S3: polishing and grinding the surface of the AgCdO / Ag-AgNi10 composite alloy, purging with nitrogen after the polishing and grinding, spraying a lubricant on the surface of the alloy, performing wire splitting and drawing, and then forming and rolling to obtain composite special-shaped wire; The lubricant preparation method is as follows: Graphite and molybdenum disulfide are mixed in a mass ratio of 1:1, ground in a ball mill at a speed of 400 r / min for 1 hour to obtain a mixture with a particle size of 800 mesh, dispersed in glycerol with a solid-liquid mass ratio of 2:1, and then 2wt% of silane coupling agent KH550 is added to the solid-liquid mixture, and stirred at a speed of 200 r / min for 1 hour to obtain the lubricant.
2. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The pre-oxidation process parameters in S1 are oxygenation in an oxygen atmosphere at a temperature of 700-800° C. for 35-45 hours.
3. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The thermal composite process parameters in S1 are 630-680° C. and a tape speed of 1.2-1.8 m / min.
4. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The polishing parameters in S3 are: first use a grinding head composed of 500-mesh elastic modules to polish at 1-2 MPa for 1 hour, and then use a grinding head composed of 2000-mesh elastic modules to polish at 0.3-0.5 MPa for 0.5 hour.
5. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The flow rate of nitrogen purge in S3 is 20 m / s, and the purge time is 0.5 h.
6. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The spraying parameters of the lubricant are spraying distance 100 mm and spraying rate 60 mm / s.
7. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The diameter of the wire obtained by the wire splitting process in S3 is 0.4-0.6 mm.
8. The process for producing composite shaped yarn with high bonding strength according to claim 1, characterized in that: The diameter of the wire obtained by the drawing process in S3 is 0.2-0.3 mm.
Citation Information
Patent Citations
Method for preparing special-shaped composite contact tape
CN101259583A
Silver-based multi-layer composite electrical contact material and preparation method thereof
CN107591257A